Analisis Pengaruh Pendapatan Keluarga, Metode Pembelajaran Dan Lingkungan Sekolah Terhadap Prestasi Belajar Siswa - M.Si, Supriyanto; M.Si, Mas'adah (eBA Journal: Journal Economics, Bussines and Accounting, 2016)
University/ College is one of the education institutions must be to create human resources have a qualified. To achieve to its goals, a university should give best performance. Thus, it is important to employ the best and qualified lecturers is influenced by some factors: their education and the development program they achieved. The objective of the very research was to find the Influece Family Income, Learning Methods and School Environment to Student Achievement At the Grate 9 Students Junior High School Darul Ulum Tapen Jombang District simultaneously and partially then to know what is dominant variable. From the result of Anova test analysis, it was found out there is significant influence from Family Income, Learning Methods and School Environment to Student Achievement At the Grate 9 Students Junior High School Darul Ulum Tapen Jombang District simultaneously and partially, next which became the dominant variable is family income.